Two Approaches of Measuring Intra-industry Trade - Sourish Dutta (Cambridge University Press (CUP), 2022)
This paper deals with the problem of measuring intra-industry trade. In section 2, it presents two existing approaches (Balboni, 2007) to measuring intra-industry trade: the so called “recovery of trade”, developed by Balassa (1966); Grubel and Lloyd (1975) & the “type of trade” one initiated by Abd-el Rahman (1986b); Vona (1991). Then this paper presents indicators and empirical methods inspired by these two approaches. Notions of trade recovery & trade type come from two different definitions of the empirical phenomena they aim to measure. This paper also discusses these definitions and the theoretical foundations in the section 3.
Keywords: 330